Measuring postharvest losses at the farm level in Malawi - Ambler, Kate; de Brauw, Alan; Godlonton, Susan (International Food Policy Research Institute, 2017)
Reducing food loss and waste are important policy objectives prominently featured in the United Nation’s Sustainable Development Goals. To optimally design interventions targeted at reducing losses, it is important to know where losses are concentrated between the farm and fork. This paper measures farmlevel postharvest losses for three main crops—maize, soy, and groundnuts—among 1,200 households in Malawi. Farmers answered a detailed questionnaire designed to learn about losses during harvest and transport, processing, and storage and which measures both total losses and reductions in crop quality. The findings indicate that fewer than half of households report suffering losses conditional on growing each crop. In addition, conditional on losses occurring, the loss averages between 5 and 12 percent of the farmer’s total harvest. Compared to nationally representative data that measure losses using a single survey question, this study documents a far greater percentage of farmers experiencing losses, though the unconditional proportion lost is similar. We find that losses are concentrated in harvest and processing activities for groundnuts and maize; for soy, they are highest during processing. Existing interventions have primarily targeted storage activities; however, these results suggest that targeting other activities may be worthwhile.